Wages and Job Mobility of Young Workers - Flinn, Christopher J. (Journal of Political Economy, 1986)
This paper presents a discrete-time version of Jovanovic's model of worker-firm matching. Descriptive evidence is presented that supports the notion that unobserved worker-firm heterogeneity is an important component in the intertemporal structure of wages for young workers. A structural econometric model of wage dynamics under worker-firm sorting is developed and estimated. Finally, a formal test of the matching model is carried out, and the matching structure on intertemporal covariances of wages is not rejected. My results indicate the necessity of jointly considering processes of turnover and wage growth when analyzing the labor market experiences of young workers.